Optimizing Costs and Outcomes for Carpal Tunnel Release Surgery: A Cost-Effectiveness Analysis from Societal and Health-Care System Perspectives. (1st December 2021) - Rogers, Miranda J.; Stephens, Andrew R.; Yoo, Minkyoung; Nelson, Richard E.; Kazmers, Nikolas H.
Abstract : Background: It is unclear which carpal tunnel release (CTR) strategy (i.e., which combination of surgical technique and setting) is most cost-effective. A cost-effectiveness analysis was performed to compare (1) open CTR in the procedure room (OCTR/PR), (2) OCTR in the operating room (OCTR/OR), and (3) endoscopic CTR in the operating room (ECTR/OR). Methods: A decision analytic model was used to compare costs and health utilities between treatment strategies. Utility and probability parameters were identified from the literature. Medical costs were estimated with Medicare ambulatory surgical payment data. Indirect costs were related to days out of work due to surgical recovery and complications. The effectiveness outcome was quality-adjusted life years (QALYs). Probabilistic sensitivity analyses and one-way sensitivity analyses were performed. Cost-effectiveness was assessed from the societal and health-care system perspectives with use of a willingness-to-pay threshold of $100, 000/QALY. Results: In the base-case analysis, OCTR/PR was more cost-effective than OCTR/OR and ECTR/OR from the societal perspective. The mean total costs and QALYs per patient were $29, 738 ± $4, 098 and 0.88 ± 0.08 for OCTR/PR, $30, 002 ± $4, 098 and 0.88 ± 0.08 for OCTR/OR, and $41, 311 ± $4, 833 and 0.87 ± 0.08 for ECTR/OR. OCTR/PR was also the most cost-effective strategy from the health-care system perspective. These findings were robust in the probabilistic sensitivity analyses: OCTR/PR was the dominant strategy (greater QALYs at a lower cost) in 55% and 61% of iterations from societal and health-care system perspectives, respectively. One-way sensitivity analysis demonstrated that OCTR/PR and OCTR/OR remained more cost-effective than ECTR/OR from a societal perspective under the following conditions: $0 surgical cost of ECTR, 0% revision rate following ECTR, equalization of the return-to-work rate between OCTR and ECTR, or 0 days out of work following ECTR. OCTR/OR became more cost-effective than OCTR/PR with the median nerve injury rate tripling and doubling from societal and health-care system perspectives, respectively, or if surgical direct costs in the PR exceeded those in the OR. Conclusions: Compared with OCTR/OR and ECTR/OR, OCTR/PR minimizes costs to the health-care system and society while providing favorable outcomes. Level of Evidence: Economic and Decision Analysis Level III . See Instructions for Authors for a complete description of levels of evidence.